Patients with enthesitis related arthritis show similar monocyte function pattern as seen in adult axial spondyloarthropathy - Shruti Bhattacharya; Ramnath Misra; Amita Aggarwal (BMC, 2020)
Abstract Background Axial SpA and Enthesitis related arthritis (ERA) patients show strong HLA-B27 association, gut dysbiosis, high toll like receptor (TLR)2 and 4 expression on monocytes, pro-inflammatory cytokine production and elevated levels of TLR4 endogenous ligands [tenascin-c (TNC) and myeloid related protein (MRP)8/14] in serum. Hence, we aimed to understand if these diseases have similar or different monocyte response. Methods Fifty adult axial SpA, 52 ERA patients and 25 healthy controls (HC) were enrolled. Cytokine-producing monocyte frequency before and after stimulation with lipopolysaccharide (LPS), peptidoglycan (PG), TNC or MRP8 were measured in whole blood (WB) and synovial fluid mononuclear cells (SFMC) by flow cytometry. Also, IL-6, TNF, MMP3, TNC and MRP8/14 levels were measured in unstimulated and TLR ligand stimulated WB cultures supernatant by ELISA. Finally, the mRNA expression levels of TNF and IL-6 were measured post stimulation with LPS, TNC and MRP8. Results At baseline, ERA and axial SpA patients showed similar TNF-α producing monocyte frequency which was higher than HC. MRP8 simulation led to increased TNF-α producing monocyte frequency in ERA than axial SpA. TNC and MRP8 stimulation led to similar IL-6 producing monocyte frequency in axial SpA and ERA patients. Baseline TNF and IL-6 producing monocyte frequency also modestly correlated with disease activity scores. TNF and IL-6 producing monocyte frequency increased in response to TLR stimulation in SFMC from both patients. In culture supernatants, axial SpA and ERA patients showed similar TNF production at baseline. MRP8 and TNC stimulation led to higher TNF production from ERA. Baseline IL-6 and MMP3 production was higher in ERA while TLR stimulation led to similar IL-6 and MMP3 production from axial SpA and ERA. TNC stimulation led to higher MMP3 production in ERA. mRNA expression in response to TLR stimulation was observed to be similar in axial SpA and ERA. TNC production was higher in ERA at baseline, while MRP8/14 production was higher in axial SpA than ERA post stimulation. Conclusion ERA patients have similar monocyte response to exogenous and endogenous TLR ligands as patients with axial SpA. This suggests that differences between pediatric and adult-onset SpA are minimal and they may have a common pathogenesis.